2018
DOI: 10.5603/kp.a2018.0173
|View full text |Cite
|
Sign up to set email alerts
|

Longevity and cardiovascular mortality of Polish elite football players

Abstract: The study results point to excess cardiovascular mortality among Polish elite footballers. A trend analysis has shown, however, that its level is falling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…The Newcastle-Ottawa scale assesses the methodological quality, and generalisability of an individual study, with higher scores indicating high methodological quality. Of a possible maximum score of 9 on the Newcastle-Ottawa quality score, five, six, nine and four papers scored nine [30][31][32][33][34], eight [35][36][37][38][39][40], seven [41][42][43][44][45][46][47][48][49] and six [50][51][52][53], respectively. Funnel plots were used to assess publication bias ( Supplementary Figures 2-4), with all-cause, CVD, and cancer mortality demonstrating publication bias, indicated by the wide range of log SMRs reported in the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Newcastle-Ottawa scale assesses the methodological quality, and generalisability of an individual study, with higher scores indicating high methodological quality. Of a possible maximum score of 9 on the Newcastle-Ottawa quality score, five, six, nine and four papers scored nine [30][31][32][33][34], eight [35][36][37][38][39][40], seven [41][42][43][44][45][46][47][48][49] and six [50][51][52][53], respectively. Funnel plots were used to assess publication bias ( Supplementary Figures 2-4), with all-cause, CVD, and cancer mortality demonstrating publication bias, indicated by the wide range of log SMRs reported in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Elite athletes may be characterised by healthier lifestyles post-retirement than the general population and engage in more leisure-time physical activity (LTPA), both of which predict all-cause mortality [31,44,57,58]. It is, therefore, not currently possible to * Gadja et al [49] presented two separate standard mortality risk (SMR) scores for ages under, and over, 65 which was impossible to separate. The star highlights the SMR for over 65's distinguish the influence of intensive training per se from overall lifestyle factors.…”
Section: All-cause Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, prothrombotic changes in the haemostatic system and haematologic indices are observed, namely: increased markers of procoagulant activity [36], increased platelet aggregability, decreased fibrinolytic activity [7,37], and increased haematocrit [38] and blood viscosity [39]. Interestingly, a recent study found that cardiovascular diseases were a more common cause of death among elite Polish footballers than in the general male population [40].…”
Section: Per-match Day Analysismentioning
confidence: 99%
“…Despite the fact that football is extremely popular globally, there is a paucity of data analyzing how competitive football playing influences life duration [ 9 , 10 , 11 ]. Moreover, the available data rarely address the issue of position occupied by football players on the pitch [ 12 ]. Football is a complex game with an inconsistent level of intensity of physical effort during the game or training.…”
Section: Introductionmentioning
confidence: 99%